PERBANDINGAN MARGIN PEMASARAN BERAS BERDASARKAN MUSIM PANEN DI KECAMATAN KAKAS BARAT - Andriano R. Manoppo; Joachim N K. Dumais; Paulus A. Pangemanan (AGRI-SOSIOEKONOMI, 2016)
This research aimed to compare the marketing margin on farmers, traders, and retailers in the harvest of last season and the season now and see rice marketing distribution channels. As a very important sector, rice is still facing many problems, especially with regard to the welfare of peasant producers. Rice marketing issues, including low selling price at the level of farmers marketing channel pattern, margin and marketing efficiency. This research was conducted in the district of West Kakas in four villages namely Tountimomor, Passo, Panasen, Kalawiran, as the biggest producer in West Kakas and this research during the month of July until completed. The data obtained are primary and secondary data. Primary data sourced from the opinions and interviews with related parties are the subject of research. Secondary data is data obtained by researchers who comes from a document from the relevant authorities, such as: internet, literature sources or literature books and the Central Bureau of Statistics. This study uses a snowball to the rice marketing channel. Based on research conducted showed that the cost and the marketing margin level channel 1 at harvest 1 lower than the cost and the marketing margin level channel 1 for the season 2, also the cost and marketing margin on channel 2 at harvest level 1 is still lower than the cost and the marketing margin at the channel level 2 for the season 2. The greater the marketing margin, the more inefficient the marketing system.